2018
DOI: 10.1186/s12871-018-0530-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of small intestinal damage in a rat model of 6 Minutes cardiac arrest

Abstract: BackgroundContribution of the small intestine to systemic inflammation after cardiac arrest (CA) is poorly understood. The objective was to evaluate whether an in vivo rat model of 6 min CA is suitable to initiate intestinal ischaemia-reperfusion-injury and to evaluate histomorphological changes and inflammatory processes in the small intestinal mucosa resp. in sera.MethodsAdult male Wistar rats were subjected to CA followed by cardio-pulmonary resuscitation. Proximal jejunum and serum was collected at 6 h, 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 45 publications
2
11
0
1
Order By: Relevance
“…Although research has shown that the reperfused intestine is characterized by severe histological alterations, mucosal rupture, and increased permeability [23], we did not find significant differences in the intestinal mucosal injury score between the three groups. Our results are similar to those of Schroeder et al who reported a mild intestinal barrier damage and mild local intestinal inflammation within 24 h post-ROSC in a rat model of six-minute cardiac arrest [25]. The mild intestinal injury in the CA-CPR group may be also explained by the low dose of the administered adrenaline, which may have minimized the detrimental effect of the drug on mesenteric blood flow [26].…”
Section: Discussionsupporting
confidence: 91%
“…Although research has shown that the reperfused intestine is characterized by severe histological alterations, mucosal rupture, and increased permeability [23], we did not find significant differences in the intestinal mucosal injury score between the three groups. Our results are similar to those of Schroeder et al who reported a mild intestinal barrier damage and mild local intestinal inflammation within 24 h post-ROSC in a rat model of six-minute cardiac arrest [25]. The mild intestinal injury in the CA-CPR group may be also explained by the low dose of the administered adrenaline, which may have minimized the detrimental effect of the drug on mesenteric blood flow [26].…”
Section: Discussionsupporting
confidence: 91%
“…Evidence from pathologic processes, including decreasing the in ammation of tissues, suppressing oxidative stress and decreasing the level of apoptosis, was observed in tissues of kidney and intestine in the CRRT group. According to a growing body of literature, TNF-α and IL-6 are typical indexes to manifest the in ammatory response of the whole body or certain organs [36]. With a smaller elevation of TNF-α and IL-6, CRRT cooling might have a protective in uence by decreasing tissue in ammation in the kidney and small intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from pathologic processes, including decreasing the in ammationof tissues, suppressing oxidative stress and decreasing the level of apoptosis,was observed in tissues of kidney and intestine in the CRRT group.According to a growing body of literature, TNF-α and IL-6 are typical indexes to manifest the in ammatory response of the whole body or certain organs [36]. With a smaller elevation of TNF-α and IL-6, CRRT cooling mighthave a protective in uence by decreasing tissue in ammation in the kidney and small intestine.…”
Section: Discussionmentioning
confidence: 99%